Extended‐release methylphenidate for attention deficit hyperactivity disorder (ADHD) in adults - Boesen, Kim (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the beneficial and harmful effects of extended‐release formulations of methylphenidate in adults diagnosed with ADHD.